A STRUGGLE FOR BEING A RAPPER IN SCOTT SILVER’S 8 MILE MOVIE : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KAWURI , SUKMAYANI (2007)
This research paper investigates how struggle to reach the goal of life especially struggle for being a rapper influences the major character’s psychological development in Scott Silver’s 8 Mile, especially viewed by individual psychological approach. Therefore, the study analyses the movie in terms of its structural elements and based on the individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two data sources: they are primary and secondary data sources. The primary data source and the object of the study is the movie 8 Mile itself, meanwhile the secondary ones are any books of literature and psychology related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. The result of the analysis shows the following conclusions: first, Scott Silver wants to utter his idea that struggle to reach a goal of life should be achieved by working hard and trying to be better than before, and second, struggle to reach a goal of life which is achieved by working hard and trying to be better will influence the psychological development of the major character. In this movie, Jimmy”Rabbit” Smith as the major character has to struggle for being a rapper which reinforces his psychological development.